Soil microbiological attributes and sugarcane productivity following implementation of three sugarcane reformation systems - Oliveira, Gabriela Moraes de; Moraes, Lucas Augusto de Assis; Silva, Adriana Pereira da; Machineski, Gabriela Silva; Missio, Francieli de Fátima; Tavares Filho, João (Semina: Ciências Agrárias, 2024)
The increasing demand for biofuels has driven the Brazilian sugarcane industry to expand into degraded pasture areas with low organic matter content and fertility. Traditionally, sugarcane is cultivated in sandy soils, and after five or more harvest cycles, field reform involves conventional tillage, followed by sugarcane planting in the exposed soil. However, the introduction of cover crops during this reform period has shown soil fertility benefits, although research on soil microbiology impacts is limited. This study aimed to evaluate soil microbiological attributes and sugarcane productivity following the implementation of three different reform systems in a sandy Ultisol. The three systems assessed were conventional planting in exposed soil and field reform using either soybean or Crotalaria spectabilis. Ten samples were randomly collected from a 10-hectare plot at a depth of 0.00-0.10 m, near the planting furrow, for each management system. The samples were analyzed for organic carbon, microbial biomass carbon, total glomalin, easily extractable glomalin, and sugarcane productivity. Data were subjected to an analysis of variance and means were compared using Tukey's test. The findings indicate that cultivating C. spectabilis before planting sugarcane enhances soil health and mitigates the impacts of agricultural practices. This improvement is attributed to higher levels of microbial biomass carbon, easily extractable glomalin, and total glomalin, which contribute to increased sugarcane productivity.